Implication of ICT in Libraries of Higher Education Institutes: A Panacea Catapulting Library Development in Africa - Abdullahi Kamba, Manir (DESIDOC Journal of Library & Information Technology, 2010)
The Information Age transformed developed nations in the tale end of the 20th century, and now is poised to have an equally dramatic effect on developing nations. Information and Communication Technology (ICT) has helped higher education libraries improve the provision of library and information resources and services. African libraries are also adopting ICT to improve and also give a positive impact to the development of research and information utilisation. The key success factor of this implementation is mainly of availability and the good quality of grade of services, adequate resources, and communication infrastructure. The paper has analysed the efforts made by the higher education libraries in Africa to recognise, restructure and re-oriented the library facilities and personnel with ICT adoption. In addition, the paper also highlights the various efforts to establish networking and consortia among the libraries, and the implications that could be derived by applying ICTs into higher education libraries. The paper also highlights the reasons why ICT application is taking a snail speed in library development in Nigeria and provides the solutions as a panacea for library development in Africa. http://dx.doi.org/10.14429/djlit.31.1.765